Increasing Torque Capacity on Clutch Made From Coconut Fiber Composite: Peningkatan Kapasitas Torsi pada Kopling Berbahan Komposit Sabut Kelapa - Purboputro, Pramuko Ilmu; Hendrawan, Muh. Alfatih (Prosiding University Research Colloquium, 2023)
The aim of this study is to investigate composition of coconut fiber, copper powder, fiberglass and phenolic resin as matrice for material of motorcycle clutch. The coconut fiber is in the dicontinuous fiber, for subtituting asbestos componen that unfair for lung healty and environmental issues. The result were compared with existing clutch product SGP for their hardness, wearness and their friction coefficient in wet and dry condition. The method was materials compacted in 2 tons pressure during 60 minutes holding time, then sintered on 800C at 40 minutes holding time, and take out from oven, then it conduct on Brinell hardness tester, and wearing test according ASTM F 1957-99 and ASTM D 3702-94 standard of testing materials The result shown that composition with 40% weight of coconut fiber, 20% copper powder, 20% fiberglass and 20% phenolic resin given 4.098 kg/mm2 on hardness number. Wearing at dry condition is 0,14 mm/hr and 0,19 mm/hr on oil wet condition. The exising material was SGP with 3,974 kg/mm2 hardness, its wearing on dry condition was 0,15 mm/hr and 0,20 mm/hr, on oil wet condition.